2010
DOI: 10.1053/j.sempedsurg.2009.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Growth factors: possible roles for clinical management of the short bowel syndrome

Abstract: The structural and functional changes during intestinal adaptation are necessary to compensate for the sudden loss of digestive and absorptive capacity after massive intestinal resection. When the adaptive response is inadequate, short bowel syndrome (SBS) ensues and patients are left with the requirement for parenteral nutrition and its associated morbidities. Several hormones have been studied as potential enhancers of the adaptation process. The effects of growth hormone (GH), insulin-like growth factor-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 108 publications
(100 reference statements)
0
37
0
1
Order By: Relevance
“…Approximately 20,000 patients in this country are on home TPN. A reduction of just 10% would result in estimated savings of $780,000,000 (27).…”
mentioning
confidence: 99%
“…Approximately 20,000 patients in this country are on home TPN. A reduction of just 10% would result in estimated savings of $780,000,000 (27).…”
mentioning
confidence: 99%
“…Asimismo, se han utilizado factores de crecimiento y otras hormonas tróficas para mejorar la adaptación intestinal (32). La hormona de crecimiento humana recombinante fue el primer medicamento aprobado por la Food and Drug Administration (FDA) con indicación específica en SIC combinado con glutamina y optimización/modificaciones de la dieta.…”
Section: Tratamientos Sintomáticos Del Síndrome De Intestino Cortounclassified
“…Laboratory studies have shown that GH causes mucosal hyperplasia and increases the adaptive capacity after small resection [83,84]. Other actions of GH include enhancement of the villus height and crypt depth, positive nitrogen balance and bowel growth when rats were given GH combined with glutamine and/or a diet high in protein [85,86].Studies in children with PSBS showed a reduction in PN [87], but after cessation of GH the positive response could not be preserved [88)]. The results in adults are controversial.…”
Section: Growth Hormone (Gh)mentioning
confidence: 99%